The influence of Tawhidic paradigm on the development of a unified theory of the firm - Mhd. Sarif, Suhaimi (2013)
This study argues on the influence of Tawhidic paradigm to a unified theory of the firm from for a comprehensive theory to describe the nature of the firm, the scope and boundaries of assessment on organizational environments, and the assessment of internal organizations to formulate, implement and evaluate organizational strategies. The conventional approach to the theory of the firm is not adequate to respond to external, internal, and human dynamism. The study used qualitative method via personal interview 15 senior managers of Islamic financial institutions that listed in Bursa Malaysia. The informants argued that the vision, mission and objective statements that differentiate the shari’ah compliant and non-shari’ah compliant companies. The shariah-compliant companies apply Tawhidic paradigm in terms of companies’ continuous improvement in all functional aspects, value added services to the stakeholders, and enhancing social welfare to the humanity. The use of qualitative method through personal interviews is appropriate for exploratory nature of the study to develop a unified theory of the firm. Nevertheless, the findings cannot be generalizable. However, the study contributes a contemporary framework of the theory of the firm from Tawhidic paradigm, which adds into the sustainability principles and business continuity.